Overcoming cancer risk in inflammatory bowel disease: new insights into preventive strategies and pathogenesis mechanisms including interactions of immune cells, cancer signaling pathways, and gut microbiota - Zhang, Haonan; Shi, Yulu; Lin, Chanchan; He, Chengcheng; Wang, Shanping; Li, Qingyuan; Sun, Yan; Li, Mingsong (Frontiers in Immunology, 2024)
Inflammatory bowel disease (IBD), characterized primarily by gastrointestinal inflammation, predominantly manifests as Crohn's disease (CD) and ulcerative colitis (UC). It is acknowledged that Inflammation plays a significant role in cancer development and patients with IBD have an increased risk of various cancers. The progression from inflammation to carcinogenesis in IBD is a result of the interplay between immune cells, gut microbiota, and carcinogenic signaling pathways in epithelial cells. Long-term chronic inflammation can lead to the accumulation of mutations in epithelial cells and the abnormal activation of carcinogenic signaling pathways. Furthermore, Immune cells play a pivotal role in both the acute and chronic phases of IBD, contributing to the transformation from inflammation to tumorigenesis. And patients with IBD frequently exhibit dysbiosis of the intestinal microbiome. Disruption of the gut microbiota and subsequent immune dysregulation are central to the pathogenesis of both IBD and colitis associated colorectal cancer (CAC). The proactive management of inflammation combined with regular endoscopic and tumor screenings represents the most direct and effective strategy to prevent the IBD-associated cancer.